The Effect of Coping Strategies on Time Management Among Working University Students - Eva Nuraulia; Munifah Munifah; Azam Arifyadi; Ikhlas Rasido (FKIP - Universitas Riau, 2026)
This study is motivated by the demands faced by working students in balancing academic responsibilities and work through effective time management. The aim of this research is to analyze the influence of coping strategies on time management among working students in the Department of Education, Universitas Tadulako. This study employed a quantitative approach with a simple linear regression design. The population of this study consisted of working students in the Department of Education, with a sample of 60 students selected using a purposive sampling technique. Data were collected through a Likert-scale questionnaire that had met the validity and reliability tests. The results of the simple linear regression analysis showed that adaptive coping strategies had a positive and significant effect on time management (Sig. = 0.001 < 0.05; t = 11.745). Descriptive analysis results indicated that most students have adaptive coping strategies and good time management. These findings suggest that adaptive coping strategies contribute to improving the time management of working students, although they are not the only factor influencing it.